P2P Traffic Identification Based Over-Sampling Technique - Yaguan Qian; Min Zhang (Dianxin kexue)
A new approach that transfers the multi-class imbalanced problem into simple two-class imbalanced problem was proposed, and a mended SMOTE over-sampling algorithm to enrich the P2P concept was applied. The experimental results show the approach can efficiently improve the P2P identifying rate using the Naïve Bayes model.